Preliminary crystallographic studies of an anti-HIV-1 protease antibody that inhibits enzyme activity - Lescar, Julien; Štouračová, Renata; Riottot, Marie-Madeleina; Chitarra, Véronique; Brynda, Jiří; Fábry, Milan; Hořejší, Magdalena; Sedláček, Juraj; Bentley, Graham A (Protein science, 1996)
F11.2.32, a monoclonal antibody directed against the HIV-1 protease, displays strong inhibitory effects toward the catalytic activity of the enzyme. The antibody cross-reacts with peptides 36-46 and 36-57 from the protease. Crystals of the Fab have been obtained both in the free state and as complexes formed with the protease peptide fragments, 36-46 and 36-57. Diffraction data have been collected for the free and complexed forms of Fab F11.2.32 and preliminary models for the crystal structures were obtained by molecular replacement.
Keywords: HIV Protease Inhibitors; HIV-proteasa; HIV Protease; rekombinantní fúzní proteiny; Mice, Inbred BALB C; Mice; zkřížené reakce; myši inbrední BALB C; zvířata; monoklonální protilátky; HIV Antibodies; Antibodies, Monoclonal; Crystallography, X-Ray; imunoglobuliny - Fab fragmenty; Peptide Fragments; inhibitory HIV-proteasy; krystalografie rentgenová; peptidové fragmenty; HIV Antigens; myši; Animals; Immunoglobulin Fab Fragments; HIV-1; HIV antigeny; Cross Reactions; Recombinant Fusion Proteins; HIV protilátky